Contributions of a Strengthened Early Holocene Monsoon and Sediment Loading to Present‐Day Subsidence of the Ganges‐Brahmaputra Delta. Issue 3 (15th February 2018) - Karpytchev, M.; Ballu, V.; Krien, Y.; Becker, M.; Goodbred, S.; Spada, G.; Calmant, S.; Shum, C. K.; Khan, Z.
Abstract: The contribution of subsidence to relative sea level rise in the Ganges‐Brahmaputra delta (GBD) is largely unknown and may considerably enhance exposure of the Bengal Basin populations to sea level rise and storm surges. This paper focuses on estimating the present‐day subsidence induced by Holocene sediment in the Bengal Basin and by oceanic loading due to eustatic sea level rise over the past 18 kyr. Using a viscoelastic Earth model and sediment deposition history based on in situ measurements, results suggest that massive sediment influx initiated in the early Holocene under a strengthened South Asian monsoon may have contributed significantly to the present‐day subsidence of the GBD. We estimate that the Holocene loading generates up to 1.6 mm/yr of the present‐day subsidence along the GBD coast, depending on the rheological model of the Earth. This rate is close to the twentieth century global mean sea level rise (1.1–1.7 mm/yr). Thus, past climate change, by way of enhanced sedimentation, is impacting vulnerability of the GBD populations. Plain Language Summary: This paper estimates the land subsidence induced by sediments deposited in the Bengal Basin and by the sea level rise over the past 18, 000 years. The results of numerical modeling demonstrate that the coast of the Ganges‐Brahmaputra delta subsides at a rate of about 1–1.6 mm/yr depending on the lithospheric thickness and the Earth mantle viscosity. This is comparable to the rate of global mean sea level rise during the twentieth century. Thus, the intense sedimentation generated by climate changes in the past contributes significantly to the present‐day subsidence of the Bengal coast. Key Points: Holocene sediment/ocean loads generate up to 1.6 mm/yr of the present‐day subsidence in the Ganges‐Brahmaputra delta Highest subsidence rates occur at the Bengal coast and the subaqueous delta Past climate affects present‐day vulnerability of the Bengal Basin populations